Surgical mentorship in low‐resource environments: Opportunities and challenges, a perspective - Wireko A. Awuah; Joecelyn K. Tan; Hareesha R. Bharadwaj; Nicholas Aderinto; Tomas Ferreira; Heli Patel; Muhammad H. Shah; Abhay A. Kapoor; Sumitaksha Banerjee; Toufik Abdul‐Rahman; Oday Atallah (Health Science Reports)
Abstract Background and aims In low‐ and middle‐income countries (LMICs), a shortage of skilled surgical practitioners hampers healthcare delivery, impacting well‐being and economic growth. Surgical mentorship programs offer a promising solution but face challenges in implementation. This review aims to comprehensively assess the impact of surgical mentorship programs in LMICs and identify challenges and opportunities for their development and implementation. Methods A thorough literature search was conducted from 2000 to 2023 using multiple databases, focusing on surgical mentorship programs in LMICs. Inclusion criteria encompassed full‐text articles in English that demonstrated characteristics of mentorship. Rigorous exclusion criteria were applied to ensure high‐quality evidence inclusion. Results Surgical mentorship programs in LMICs strengthen local surgical capacity, improve surgical skills and patient outcomes, optimize resources and technology utilization, and positively impact medical students aspiring to be surgeons. However, challenges such as resistance to change, resource limitations, financial constraints, logistical and technological challenges, and time constraints hinder their implementation. Conclusion Despite challenges, surgical mentorship programs hold promise for enhancing surgical capacity and healthcare quality in LMICs. Standardized metrics for accountability, innovative funding mechanisms, collaborative partnerships for scalability, interdisciplinary integration, and leveraging virtual mentorship programs are key strategies to overcome challenges and foster sustainable learning cultures, ultimately contributing to improved healthcare equity and quality in low‐resource settings.